An economic analysis of the roses industry in Uganda - Kasozi, Apollo (Kampala: Makerere University, 1997)
Thesis (M.Sc., Agric. Econ.) - Makerere University, 1997
Includes bibliographical references (p. 69-71)
Keywords: Rose Industry -- Uganda; Roses